Tokyo ghoul : re. 8 - Ishida, Sui (Viz signature., 2018)
While Haise makes a plan to help his old friends escape from Cochlea prison without hurting any of his CCG colleagues, his mentor Kisho Arima confirms some of Haise's greatest fears about the organization.